Effectiveness of Ginger Aromatherapy and Warm Compresses on Menstrual Pain in Adolescents - Tri Sartika (Journal of Educational Innovation and Public Health, 2024)
Menstruation or menstruation is a sign that the reproductive system and organs in women are functioning. Menstruation causes various complaints such as discomfort caused by excessive bleeding during menstruation and complaints of pain known as dysmenorrhoea. Around 55 percent of women of childbearing age in Indonesia suffer from menstrual pain. Non-pharmacological therapies that can treat dysmenorrhoea are warm compresses and ginger aromatherapy. The aim of the research was to determine the effectiveness of ginger aromatherapy and warm compresses on menstrual pain in adolescents. The research design uses a quasi-experimental with control group design. The intervention group was given ginger aromatherapy and warm compresses on the first day of menstruation, while the control group was not given any intervention. Data analysis used the Mann Whitney test. The population in this study were all class IX female students at Sriwijaya Middle School, Palembang. The sampling technique used purposive sampling totaling 30 respondents. The menstrual pain scale uses the Numeric Ratting Scale (NRS). The results of the Mann Whitney test obtained a p value of 0.001, meaning that there was a difference in the pain scale in the intervention group that was given ginger aromatherapy and warm compresses for menstrual pain in teenagers compared to the control group that was not given the intervention. It is recommended that health workers intensify education regarding complementary therapies in reducing menstrual pain in adolescents.